Building a strip canoe : full-sized plans and instructions for eight easy-to-build, field-tested canoes - Gilpatrick, Gil (Fox Chapel Pub., 2010)
"After supervising the construction of more than 500 during his 30 years as an outdoor resources instructor in the school system of Skowhegan, Maine, Gil Gilpatrick shares his voice of experience through easy step-by-step instructions that will successfully guide both novice and accomplished woodworkers in the building of a sturdy, ready-to-use strip canoe. This revised and expanded second edition of Building a Strip Canoe includes plans and patterns for eight proven designs, most of which are Gil's original adaptations, and more than 100 photographs and illustrations. Also included are directions for making handwoven can seats and attractive, lightweight, stalwart paddles"--Cover, p. 4.